Data4Ag impacts for farmers and for policy - Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2019)
CTA's Data4Ag project has introduced digital solutions in Africa to assist farmers organisations in registering their members to offer targeted agricultural services. Whilst impacts from the field have been impressive, questions have been raised around the collection and use of farmer data, and the need for policy development.